Transient inverse heat conduction problem of quenching a hollow cylinder by one row of water jets. (February 2018) - Jahedi, Mohammad; Berntsson, Fredrik; Wren, Joakim; Moshfegh, Bahram
Highlights: The GMRES method is applied in quenching process by water jets. Regularization parameter and mesh size are optimized by sensitivity analysis. Temperature cyclic variation is damped from surface to interior of rotary specimen. Time delay of cooling the interior of specimen compared to surface is predicted. Three different boiling curves are defined for a quenched rotary convex surface. Abstract: In this study, a two-dimensional linear transition inverse heat conduction problem (IHCP) was solved using the Generalized Minimal Residual Method (GMRES) in quenching process by water jets. The inverse solution method was validated by set of artificial data and solution sensitivity analysis was done on data noise level, regularization parameter, cell size, etc. An experimental study has been carried out on quenching a rotary hollow cylinder by one row of subcooled water jets. The inverse solution approach enabled prediction of surface temperature and heat flux distribution of test specimen in the quenching experiments by using measured internal specimen temperature. Three different boiling curves were defined in the quenching process of a rotary cylinder. Result obtained by the inverse solution showed clear footprint of rotation in surface temperature and heat flux on each revolution of cylinder and temperature variation damping from quenching surface toward interior of specimen.